2014
DOI: 10.1007/s12132-014-9235-3
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital and Trust in Slum Areas: the Case of Addis Ababa, Ethiopia

Abstract: This study explores how social capital and socioeconomic variations in slum areas influence the fostering of social trust and confidence in the institutions. Through a multivariate analysis using 497 households in slum areas of Addis Ababa, the paper investigates how social capital dimensions and human and economic characteristics of the households are related to social trust and confidence in the institutions. It is shown that social trust and confidence in institutions are highly associated with increased pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
9
0
3
Order By: Relevance
“…A local/community association is a group/organization that works for the benefit of its members or a particular community. A community rich in structural social capital stock is assumed to be characterized by the strong engagement of residents in their local associations [46,47]. This strong engagement can be utilized to protect households from evictions [64].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…A local/community association is a group/organization that works for the benefit of its members or a particular community. A community rich in structural social capital stock is assumed to be characterized by the strong engagement of residents in their local associations [46,47]. This strong engagement can be utilized to protect households from evictions [64].…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Ref. [47] showed that increased participation in local associations among slum dwellers in Addis Ababa, Ethiopia, created a bonding and bridging type of social network that has contributed to the development of social trust and confidence in the government. Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of network is employed as a tool for a normative or critical urbanism (McFarlane 2011). Elsewhere, the idea of social capital, as developed by Pierre Bourdieu, is used as a resource for enabling network chain interactions, in particular, with a focus on trust and informal settlements (Kassahun 2015). However, the bulk of the research in this area applies the idea of social networks in a rather loose way.…”
Section: Network and Informal Settlementsmentioning
confidence: 99%
“…In contrast, slums in SSA also foster social capital, community connectedness, and a sense of belonging, all of which are critical health resources for the urban poor. Although slums have also been reported as zones of ethnic conflicts in some countries (69), they nevertheless have inspired community action against the health and social impacts of exclusion, material deprivation, and environmental decay in some places, including Francistown, Botswana (70) and Addis Ababa, Ethiopia (71).…”
Section: Neighborhood Crime and Social Capitalmentioning
confidence: 99%